FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN BRANDING SEKOLAH DALAM MENINGKATKAN MINAT PENDAFTARAN SISWA (STUDI KASUS DI SMA NEGERI 6 KOTA JAMBI - Padliyan, Reka; Pratiwi, Ngisti; Fitri, Vidia; Rifki, Ahmad (Jurnal Pendidikan Ekonomi, 2024)
This study analyzes the impact of branding strategies on student enrollment interest at SMA Negeri 6 Kota Jambi. Using a qualitative approach, data were collected through interviews, observations, and document studies from the school principal, vice principals, and students. The results show that the school's branding as a "sports school" plays a significant role in attracting students, especially those with talents in sports. Factors such as comprehensive sports facilities, academic flexibility, and non-academic achievement- based admission pathways contribute to students' decision to enroll. This research provides insights into effective branding strategies for building a school’s image amid educational competition.